The Review Analysis of Higher Education Policy Documentation: The Case of Mongolia - Selenge, Chuluun; Baigalmaa, Danzan; Bayasgalan, Tsogtsuren; Erdenetsetseg, Batkhuyag; Khishigbaigali, Erdenebat; Munkhzul, Baatar (Advances in Social Sciences Research Journal, 2024)
The aim of our study is to assess in higher education policy’s official documents, unveiling potential areas for suggest order refinement and enhancement in the formulation and communication of educational strategies. The effectiveness of policy instruments in accomplishing intended outcomes is addressed by the analysis of higher education policy documentation, which provides insights into the alignment between stated objectives and implemented